Assessment of crop usage in ad libitum fed birds and short-term phytase efficiency as affected by acid addition. Issue 3 (4th May 2022) - Kristoffersen, S.; Wiśniewska, Z.; Kaczmarek, S.; Gjefsen, T.; Kjos, N. P.; Cowieson, A. J.; Svihus, B.
ABSTRACT: 1. A field assessment was performed to map the extent of crop usage and thus retention time in broiler chickens. In addition, a broiler experiment was carried out to study the short-term effect of acid addition on phytase efficacy in the crop. 2. In the field assessment, the crop content of 40 ad libitum fed broiler chickens from 4 different farms were sampled at 10, 20 and 30 d of age. The dry matter (DM) content varied from 0 to 32 g. 3. From 11 d of age, 120 individually caged chickens were intermittently fed a high phytate-P diet with either no addition or 500 FYT C. braakii -derived phytase added or both phytase and 1.4% formic acid added. Excreta were collected for assessment of phosphorus (P) retention. At 20 and 21 d of age, starved birds were fed for 1 h, and thereafter crop and gizzard contents were collected every 20 min until 140 min after start of the feeding. At 60 and 140 min, the contents from the jejunum and ileum were collected. 4. All diets reduced the concentration of phytate in the crop, however the combination of acid and phytase resulted in a higher degradation ( P < 0.05) than the other diets from 20 min after the start of feeding. Simultaneously, the concentration of the smaller inositol phosphate isomers, such as inositol-5-phosphate, increased ( P < 0.05). Phytase increased ( P < 0.05) P retention, and the combination of acid and phytase increased jejunal P digestibility ( P < 0.05) compared to the other diets. 5. The results indicated that lower pH in the crop due to acid addition improved phytase efficacy and increased P digestibility in the anterior digestive tract, even with short retention times.